Análise dos impactos socioambientais da atividade turística em Pitangui/RN: estudo de caso sobre a percepção dos atores locais - Dantas, Noemy Luíza Silva (2021)
The tourist activity is seen as a major development factor for the destinations where it occurs, however, the negative impacts arising from Tourism in the receiving community are set aside or neglected and how it affects the reality of the local actors; with this in mind, the present work has as general objective to analyze the perception of the local actors on the socio-environmental impacts of the tourist activity in Pitangui/RN. With a qualitative-quantitative approach, the results were collected through an interview with statements in the Likert Scale (1932) and open questions with the universe of research totaling 31 respondents who were divided into five groups, Residents, Tourists, Representatives of local companies, Tourism Professionals and Tourism Managers. The results obtained through the calculation of the Average Ranking demonstrated that Tourism is seen, in general, with a positive vice by the groups and that it has brought benefits to the community. The final considerations point out that tourism, despite generating development for the community, still has room for improvement, mainly in the basic infrastructure and security in the community, making room for a more in-depth study of the locality.